2017
DOI: 10.3390/rs9121288
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of Remote Sensing Data in Monitoring Vegetation Phenology: A Comparison of MODIS C5 and C6 Vegetation Index Products on the Tibetan Plateau

Abstract: Vegetation phenology is considered a sensitive indicator of climate change, which controls carbon, nitrogen, and water cycles within terrestrial ecosystems. The Moderate Resolution Imaging Spectroradiometer (MODIS) Normalized Difference Vegetation Index (NDVI) is an important moderate resolution remote sensing data for monitoring vegetation phenology. However, Terra MODIS Collection 5 (C5) vegetation index products were identified to be affected by sensor degradation, which has been addressed in the recently r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 48 publications
2
20
0
Order By: Relevance
“…Collection 6 of the MODIS data was released in the fall of 2015. Some papers have highlighted significant sensor degradation in collection 5 and notable differences between time series in collections 5 (V005) and 6 (V006) (Wang et al 2012, Zheng and Zhu 2017, Lyapustin et al 2014. In this paper we evaluate the land surface phenology for these two collections, and we investigate how well the land surface phenology results from the two collections correlate with large scale climate indices.…”
Section: Introductionmentioning
confidence: 99%
“…Collection 6 of the MODIS data was released in the fall of 2015. Some papers have highlighted significant sensor degradation in collection 5 and notable differences between time series in collections 5 (V005) and 6 (V006) (Wang et al 2012, Zheng and Zhu 2017, Lyapustin et al 2014. In this paper we evaluate the land surface phenology for these two collections, and we investigate how well the land surface phenology results from the two collections correlate with large scale climate indices.…”
Section: Introductionmentioning
confidence: 99%
“…Another possible solution would be including more newly released MODIS reflectance product Collection 6 (C6). A recent study found that, in the Tibetan Plateau, NDVI from Collection 5 (C5) SOS was more consistent than C6 SOS in terms of ground-observed green-up dates for alpine grassland [63]. Although there was improved quality at high latitudes from use of all available observations in C6 than C5 who used only four observations per day.…”
Section: Fi-hyymentioning
confidence: 99%
“…In addition, the maximum value composite (MVC) method was used to construct the monthly NDVI data for the calculation of monthly NPP [32]. To avoid the uncertainty caused by land cover change, we only considered pixels where grassland cover type remained identical during 2001-2015, according to the criteria set in a previous study [33]: (1) the average NDVI for June-September should be greater than 0.1; (2) the annual maximum NDVI should exceed 0.15 and occur within July-September;…”
Section: Datasetsmentioning
confidence: 99%
“…In addition, the maximum value composite (MVC) method was used to construct the monthly NDVI data for the calculation of monthly NPP [32]. To avoid the uncertainty caused by land cover change, we only considered pixels where grassland cover type remained identical during 2001-2015, according to the criteria set in a previous study [33]: (1) the average NDVI for June-September should be greater than 0.1; (2) the annual maximum NDVI should exceed 0.15 and occur within July-September; (3) the average NDVI for July-September should be greater than 1.2 times the average NDVI for November-March; and, (4) the average NDVI in winter (December-February) should be lower than 0.4. In addition, the green-up (also termed as MCD12Q2derived BGS) derived from the MODIS Land Cover Dynamics Collection 6 dataset (MCD12Q2) (https://lpdaac.usgs.gov/products/mcd12q2v006/) was compared in performance with BGS derived from MOD13Q1 NDVI in this study.…”
Section: Datasetsmentioning
confidence: 99%